Resiliensi pada Anak Remaja dari Keluarga Broken Home: Resilience in Adolescents from Broken Home Families - Sandra, Revina; Sulastri, Sulastri; Proborini, Renyep (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Broken home occurs because the family structure is not intact, because the parents are divorced and the family is not harmonious. This research aims to determine the resilience process in broken home teenagers in Tanjung Senang District Bandar Lampung City. The method used in this research is a qualitative research method. The research results show the teenagers who experience broken homes can develop resilience skills with support from relatives and their mother’s family. Able to get through the critical period of 8 to 1 year in his own way, namely, doing lots of positive activities outside the home. Accept the situation, focus on achieving your dreams and making your mother happy. Take lessons from family problems and use the learning as provisions for future life.